2015
DOI: 10.1021/ja512690x
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Enabled β-C–H Arylation of α-Amino Acids Using a Simple and Practical Auxiliary

Abstract: Pd-catalyzed β-C–H functionalizations of carboxylic acid derivatives using an auxiliary as a directing group have been extensively explored in the past decade. In comparison to the most widely used auxiliaries in asymmetric synthesis, the simplicity and practicality of the auxiliaries developed for C–H activation remains to be improved. We previously developed a simple N-methoxyamide auxiliary to direct β-C–H activation, albeit this system was not compatible with carboxylic acids containing α-hydrogen atoms. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
63
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(70 citation statements)
references
References 81 publications
(68 reference statements)
0
63
0
4
Order By: Relevance
“…(3)]. Employing similar conditions to those reported in our CONHOMe-directed arylation, [10] we were pleased to find that L1 provided the desired arylated product in 45% yield (Scheme 2). A control experiment showed that no reaction occurred in the absence of ligand.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…(3)]. Employing similar conditions to those reported in our CONHOMe-directed arylation, [10] we were pleased to find that L1 provided the desired arylated product in 45% yield (Scheme 2). A control experiment showed that no reaction occurred in the absence of ligand.…”
mentioning
confidence: 74%
“…(1)]), [9,10] both of which serve as carboxylate surrogates in the Pd-catalyzed C–H activation of alanine derivatives, enabling the preparation of unnatural α -amino acids. Both of these reactions benefit from ligand acceleration by either pyridine- or quinoline-based ligands, though the installation and removal of these exogenous directing groups hampers the broad application of these methods.…”
mentioning
confidence: 99%
“…Herein, we report our discoveries on the uniquea nd intriguing role of 1,1,1,3,3,3-hexafluoropropanol (HFIP) solvent in atropo-diastereoselective, sulfoxide-directed CÀCc oupling. Notably,t his polyfluorinated alcohol stood out recently as an optimal solventf or several challenging CÀHa ctivation reactions, [19] buti ts particularr ole has remained ambiguous. The mechanistic studies presented above indicate that the key feature of our catalytic system was the formation of hydrogen-bonded complex between the substrate and solvent facilitating the CÀHa ctivation step and improving the stereochemicalo utcome of this transformation.…”
Section: Introductionmentioning
confidence: 99%
“…1c)44454647. For example, N -methoxyamide has been used as a directing group4849 for β-C( sp 3 )-H arylation with a pyridine-type ligand, affording various non-natural amino acids from protected alanine derivatives49. These developments have greatly expanded the possible approaches to construct key structures of natural products, pharmaceutical agents and organic materials.…”
mentioning
confidence: 99%